Software as a Service and Habeas Data: An Approach from Private and Constitutional Law in Colombia - Mendoza Munar, Lainiver (DIXI, 2018)
Theme and scope: This reflection paper aims to analyze personal data processing in Colombia by companies that offer software as a service (SaaS), especially the regulation regarding habeas data in Colombia and related principles established by case law. Characteristics: Various contractual types are analyzed from private law and the importance of regulat- ing personal data processing in the platforms providing the SaaS service is determined, based not only on constitutional principles, but also on the use of private law regulations. Findings: The application of constitutional principles plays a significant role when regulating the con- tractual types of technology companies, although contracts are also crucial according to the principles laid down by the law and case law on personal data. Conclusions: We could demonstrate the importance of determining product ownership and data own- ership, as well as the relevance of stipulating these aspects in the technological platforms using the SaaS model to operate in Colombia.